What Matters to Us: Impact of Telemedicine During the Pandemic in the Care of Patients With Sarcoma Across Scotland. (2021) - McCabe, Holly M.; Smrke, Alannah; Cowie, Fiona; White, Jeff; Chong, Peter; Lo, Steven; Mahendra, Ashish; Gupta, Sanjay; Ferguson, Michelle; Boddie, David; Mmekka, Walter; Stirling, Lorraine; et al.
Abstract : PURPOSE: In Scotland, approximately 350 sarcoma cases are diagnosed per year and treated in one of the five specialist centers. Many patients are required to travel long distances to access specialist care. The COVID-19 pandemic brought a number of rapid changes into the care for patients with cancer, with increasing utilization of telemedicine. We aimed to evaluate how the utilization of telemedicine affects professionals and patients across Scotland and care delivery, at the Beatson West of Scotland Cancer Centre Sarcoma Unit. METHODS: Between June 8 and August 25, 2020, we invited patients and professional sarcoma multidisciplinary team members to participate in separate online anonymous survey questionnaires, to assess their attitudes toward telemedicine. Data were extracted, and descriptive statistics were performed. RESULTS: Patient satisfaction (n = 64) with telemedicine was high (mean = 9.4/10) and comparable with traditional face-to-face appointments (mean = 9.5/10). Patients were receptive to the use of telemedicine in certain situations, with patients strongly opposed to being told bad news via telemedicine (88%). Providers recommended the use of telemedicine in certain patient populations and reported largely equivalent workloads when compared with traditional consultations. Providers reported that telemedicine should be integrated into regular practice (66%), with patients echoing this indicating a preference for a majority of telemedicine appointments (57%). CONCLUSION: Telemedicine in sarcoma care is favorable from both clinician and patient perspectives. Utilization of telemedicine for patients with rare cancers such as sarcomas is an innovative approach to the delivery of care, especially considering the time and financial pressures on patients who often live a distance away from specialist centers. Patients and providers are keen to move toward a more flexible, mixed system of care.